Construção e validação do diagnóstico de enfermagem ressecamento ocular em pacientes adultos internados em unidade de terapia intensiva - Araújo, Jéssica Naiara de Medeiros (2019)
This study aimed to validate the nursing diagnosis Ocular dryness in adult patients hospitalized in an intensive care unit (ICU). This is a methodological research of validation of nursing diagnosis developed in three interrelated stages, namely: STAGE 1: Construction of the nursing diagnosis Ocular dryness in adult patients hospitalized in an ICU and of the definitions, based on the concept analysis framework and operationalized through Scoping Review. STAGE 2: Analysis of diagnostic content, in which the evaluators judged the adequacy of previously created concepts, through focus group. STAGE 3: Clinical validation of nursing diagnosis Ocular dryness in adult patients hospitalized in an ICU, performed by means of a study of the accuracy of clinical indicators of nursing diagnosis Ocular dryness, with a cross-sectional design and quantitative approach, performed with 206 patients hospitalized in an ICU of adults of a university hospital located in the Brazilian northeast. The data collected was organized and stored in a database built in Microsoft Office Excel 2016 and analyzed by a specific statistical program. The study obtained a favorable opinion from the Research Ethics Committee under number 918.510 and CAAE 36079814.6.0000.5537. The recommendations of Resolution nº 466/12, approved by the National Health Council of the Ministry of Health, on December 12, 2012, were obeyed. In the first stage, 169 articles were selected and two attributes, 32 antecedents and 12 consequent ones were identified. In the second stage, after discussion in the focus group, the judges obtained a consensus regarding the adequacy of each component and definition of the diagnosis. We defined 14 defining characteristics, nine related factors, two populations at risk and 20 associated conditions. In the third stage, was verified using the latent class model the prevalence of nursing diagnosis Ocular dryness in 76.22% of the sample. The clinical indicators Decreased lacrimal volume and Excess mucoid secretion presented high values of specificity. In addition, Dilated blood vessels on the ocular surface, Excess mucoid secretion, Mucoid filament and Chemosis presented higher values for sensitivity. The related factor that obtained statistical significance with the diagnosis was Lagoftalmia and the associated conditions were: Decreased blink mechanism, Medications that alter ocular surface homeostasis with reduction of lacrimal volume, Mechanical ventilation, Systemic diseases that alter ocular surface homeostasis with reduction of lacrimal volume, Absence of corneal-eyelid reflex, Absence of response to reflexes of pairs of cranial nerves III, Absence of response to reflexes of pairs of cranial nerves IV and Absence of response to reflexes of pairs of cranial nerves VI. It is concluded that the data obtained can contribute to a better understanding of the manifestation of the diagnosis in adults hospitalized in an ICU, as well as the most important signs for inference of Ocular dryness. Thus, the nursing diagnosis Ocular dryness is valid in adult patients admitted to the ICU.